ANALYZING SERVICE BARRIERS AND RISK FACTORS FOR REENTRY AMONG FORMERLY INCARCERATED ADULTS - Sepulveda, Agustina Alejandra (2020)
Recidivism is a growing problem affecting formerly incarcerated adults struggling with reentry into society. After release, most individuals are dealing with barriers in their environment that affect their access to substance abuse and mental health treatment, which can be important to reducing recidivism. Thus, this study sought to understand the various service barriers and risk factors to reentry among formerly incarcerated individuals to help increase awareness of some of the challenges the reentry population is facing. Self-administered surveys focusing on housing, employment, public assistance, and mental health barriers were collected among formerly incarcerated individuals from Southern California (n=103). Bivariate chi-square analyses and multivariate logistic regressions were used to identify significant barriers to service receipt and to understand the effects of barriers on the receipt of services while controlling for demographics. The most common barriers included housing, denial of housing due to criminal history, and employment barriers, which did not emerge as significant predictors of services; only two barriers were significant. Specifically, receiving public assistance (an indicator of poverty) increased the odds of receiving substance abuse services whereas having a mental health diagnosis increased the odds of receiving mental health services; interestingly, participation in drug court only increased the odds of receiving mental health services but approached significance for substance abuse services. These findings suggest that services such as drug court may assist formerly incarcerated adults obtain mental health treatment and that receiving services to meet their basic needs may help obtain substance abuse treatment. Social work advocacy should focus on providing similar programs to improve the chances of successful reintegration in the community